THE NEUROPSYCHOLOGICAL PROFILE OF OLDER ADULT INSTRUMENTAL MUSICIANS. (11th November 2018) - Strong, J V; Mast, B; Midden, A; Leritz, E
Abstract: Previous research suggests that individuals with musical training may show better performance compared to non-musicians in some neurocognitive domains. The purpose of these studies was to examine neuropsychological performance across levels of previous musical training in healthy older adults, examining how musical training impacts normal cognitive aging. Results showed that musical training had a positive effect on some neuropsychological test scores, including those that measure executive functioning, visual spatial ability, and language, but not on tests of attention, processing speed, or memory. Results also found that older adult musicians who continue to play show benefit in executive functioning over musicians who retire from playing, but musician groups remain equivalent regardless of their current play status in other domains, including language. Results suggest that music training has long-lasting impact on the brain's functioning, including during the normal cognitive aging process.